‘The Uniting Church’ - Hebert, Gabriel (Scottish journal of theology, 1964)
‘The Uniting Church’ has been chosen as the name for the proposed united church which is to be composed of the Gongregationalist, Methodist and Presbyterian Churches in Australia, which is described in the Final Report of the Joint Commission of the three Churches which was published in Australia in April of this year.1 The Report includes a Basis of Union which is now submitted to the responsible authorities of the three Churches for full discussion and for final decision.It is impossible in a brief article to do more than summarise what is set out carefully and in detail in the Report itself. It is however a document of great importance, since it recommends union on an episcopal basis; and this is the first time that such a proposal has been made in a Joint Commission set up by non-episcopal churches.Some three years ago we had Part I of their Report, entitled The Faith of the Church—not, be it noted, ‘The doctrinal beliefs of the three churches concerned’, but rather ‘the faith which the Church has held from the beginning’. This is completed by the final Report now published, setting out the doctrine of the Church, the Sacraments and the Ministry, and not envisaging any mere amalgamation of the three church orders, but having in view the structure of the Church as it has been from the beginning and as it was reconsidered at the Reformation.